2014
DOI: 10.1016/j.sbspro.2014.09.249
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Elementary School Students’ Mathematics Self Concept

Abstract: Mathematics self-concept, which can be defined as student ratings of their skills, ability, enjoyment and interest in mathematics, is seen as an important factor in mathematics education. In this context, the purpose of this study was to investigate the elementary school students' mathematics self-concept levels regarding their grade level and gender. Relational survey method was used in this study. The research sample were composed of 281 students, determined by randomly from in a primary and a secondary scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 20 publications
0
20
0
2
Order By: Relevance
“…Other researchers have reported contradictory findings, including Erdogan and Sengul (2014) and Zahra et al (2010). Their findings indicated a negative and insignificant relationship between mathematics achievement and academic self-concept.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other researchers have reported contradictory findings, including Erdogan and Sengul (2014) and Zahra et al (2010). Their findings indicated a negative and insignificant relationship between mathematics achievement and academic self-concept.…”
Section: Discussionmentioning
confidence: 92%
“…It is a product of a student's effort and confidence in mathematics. Though some studies have highlighted the link between academic self-concept and achievement (Erdogan & Sengul, 2014;Kwena, 2007;Osei, 2014), they have not specifically isolated mathematics self-concept. Other studies in the area have found significant relationships between academic self-concept and gender on achievement in the science subjects (Manger & Eikeland, 2006;Visi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that for three cohorts of predominantly white Australian ( n = 1,333), German ( n = 4,688), and US ( n = 2,378) secondary school students, mathematics self-concept declined across time. Erdogan and Şengul (2014) found the same pattern of decline in mathematics self-concept in a further context (Istanbul, Turkey) in a year-long study of 281 primary to secondary school students (Grades 4–6).…”
Section: Introductionmentioning
confidence: 55%
“…The importance of differences in gender norms by cultural context for mathematics self-concept was underlined in further research. A gender gap in mathematics self-concept was found in Nagy et al (2010) cross-national longitudinal study, and Erdogan and Şengul (2014) year-long study of Turkish students. Nagy et al (2010) reported that boys’ level of mathematics self-concept was consistently greater than that of girls across the cultural contexts of Germany, Australia, and the US, although mathematics self-concept declined across time for both genders.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation